The Pregnancy in Non-Communicating Rudimentary Horn of Unicornuate Uterus: A Case Report - Sanaz Mousavi; Farrin Rajabzadeh; Maryam Mohammadiyoushanloie; maasoumeh saleh (Case Reports in Clinical Practice, 2022)
A unicornuate uterus with a non-communicating rudimentary horn has always been a notorious uterine malformation threatening normal pregnancy continuation. Pregnancy in the rudimentary horn of the uterus is rare, but it plays an essential role in maternal morbidity and mortality. Early detection of rudimentary horn pregnancy is vital because poor musculature can lead to the dangerous complication of uterine rupture. When a Rudimentary horn pregnancy is diagnosed, surgical treatment to excision the horn with ipsilateral salpingectomy is recommended because of its high risk of rupture in the second trimester. We present a case of non-communicating rudimentary horn pregnancy that was terminated, and the rudimentary horn was resected.